2009
DOI: 10.1007/s12031-009-9319-z
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 Receptor Deletion Results in Circadian Changes of Locomotor and Metabolic Activity

Abstract: Interleukin-15 (IL-15) is a cytokine produced in the normal brain that acts on its specific receptor IL-15Rα and co-receptors IL-2Rβ and IL-2Rγ in neuronal cells. The functions of the cerebral IL-15 system, however, are not yet clear. To test the hypothesis that IL-15Rα regulates metabolic activity and body temperature, we quantified the specific metabolic phenotype of IL-15Rα knockout mice. These normal-appearing mice were leaner with lower fat composition. During the entire circadian cycle, the knockout mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
69
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 25 publications
11
69
1
Order By: Relevance
“…This is interesting, given that muscle/lean muscle mass ratios of non-skeletal muscle organs from IL-15Rα-KO mice, such as the heart, spleen, and kidneys, were not significantly different from those of B6129 controls. These data demonstrate a preferential effect of loss of IL-15Rα on normalized skeletal muscle weight, which may reflect alterations in overall body metabolism, as previously suggested (14). He et al (14) measured horizontal and vertical beam breaks in a metabolic chamber and reported a significant increase in activity levels of female IL-15Rα-KO compared with control mice.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This is interesting, given that muscle/lean muscle mass ratios of non-skeletal muscle organs from IL-15Rα-KO mice, such as the heart, spleen, and kidneys, were not significantly different from those of B6129 controls. These data demonstrate a preferential effect of loss of IL-15Rα on normalized skeletal muscle weight, which may reflect alterations in overall body metabolism, as previously suggested (14). He et al (14) measured horizontal and vertical beam breaks in a metabolic chamber and reported a significant increase in activity levels of female IL-15Rα-KO compared with control mice.…”
Section: Discussionsupporting
confidence: 77%
“…These data demonstrate a preferential effect of loss of IL-15Rα on normalized skeletal muscle weight, which may reflect alterations in overall body metabolism, as previously suggested (14). He et al (14) measured horizontal and vertical beam breaks in a metabolic chamber and reported a significant increase in activity levels of female IL-15Rα-KO compared with control mice. Similarly, we observed that male IL-15Rα-KO mice produced 6.3-fold more wheel revolutions compared with B1629 control mice in cage wheel running experiments and had a larger number of ambulatory photobeam breaks in the light and dark cycles.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Interleukin (IL)-15a (cytokine-specific receptor) knockout mice have been shown to exhibit a leaner phenotype with lower fat composition, elevated home-cage activity and heat dissipation (light and dark phases), greater food intake (light phase only), and raised oxygen consumption (light phase only) (He et al 2010). In the present study, an eQTL for IL15 was mapped to Chr.…”
Section: Identification Of Potential Candidate Genesmentioning
confidence: 91%